An update of preimplantation genetic diagnosis in gene diseases, chromosomal translocation, and aneuploidy screening - Chang, Li-Jung (The Korean Society for Reproductive Medicine, 2011)
Preimplantation genetic diagnosis (PGD) is gradually widely used in prevention of gene diseases and chromosomal abnormalities. Much improvement has been achieved in biopsy technique and molecular diagnosis. Blastocyst biopsy can increase diagnostic accuracy and reduce allele dropout. It is cost-effective and currently plays an important role. Whole genome amplification permits subsequent individual detection of multiple gene loci and screening all 23 pairs of chromosomes. For PGD of chromosomal translocation, fluorescence in-situ hybridization (FISH) is traditionally used, but with technical difficulty. Array comparative genomic hybridization (CGH) can detect translocation and 23 pairs of chromosomes that may replace FISH. Single nucleotide polymorphisms array with haplotyping can further distinguish between normal chromosomes and balanced translocation. PGD may shorten time to conceive and reduce miscarriage for patients with chromosomal translocation. PGD has a potential value for mitochondrial diseases. Preimplantation genetic haplotyping has been applied for unknown mutation sites of single gene disease. Preimplantation genetic screening (PGS) using limited FISH probes in the cleavage-stage embryo did not increase live birth rates for patients with advanced maternal age, unexplained recurrent abortions, and repeated implantation failure. Polar body and blastocyst biopsy may circumvent the problem of mosaicism. PGS using blastocyst biopsy and array CGH is encouraging and merit further studies. Cryopreservation of biopsied blastocysts instead of fresh transfer permits sufficient time for transportation and genetic analysis. Cryopreservation of embryos may avoid ovarian hyperstimulation syndrome and possible suboptimal endometrium.